Penggunaan Pembelajaran Berbasis Proyek Dalam Pendidikan Kewirausahaan: Analisis Bibliometrik - Ria Lestari; Henny Indrawati; Caska Caska; Neni Hermita; Afrianto Afrianto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to conduct a bibliometric analysis of literature discussing the experience of using the project-based learning (PjBL) model in creative and entrepreneurship education. The method used is descriptive bibliometric analysis. The research results show increasing interest in PjBL in education, influenced by changes in the curriculum which emphasize project-based learning experiences and the role of technology in facilitating learning. PjBL not only improves technical skills but also soft skills such as communication, collaboration and time management, which are much needed in the modern world of work. The integration of technology in PjBL enables more interactive and interesting learning, increasing student engagement and motivation. In addition, this research highlights the importance of collaboration between researchers, educators and practitioners in developing learning models that are effective and relevant to the needs of industry and society. With a better understanding of user experiences in the PjBL context, learning practices can be developed more effectively to prepare future generations to face global challenges with creativity and confidence